KINESTHETIC APPROACHES TO FOREIGN LANGUAGE VOCABULARY ACQUISITION - Makhmashayeva Dinara Tilovmurodovna (International Journal of Literature and Language Studies, 2026)
Abstract. This article explores the effectiveness of kinesthetic approaches in foreign language vocabulary acquisition. The study is based on the analysis and synthesis of previous research related to physical movement, embodied learning, and vocabulary teaching strategies such as Total Physical Response (TPR), gestures, and classroom-based physical activities. The findings show that kinesthetic learning significantly improves students’ memory retention, cognitive processing, and motivation in vocabulary learning. The study concludes that integrating physical movement into language instruction creates more engaging and effective learning environments, leading to better vocabulary acquisition and long-term retention.